Domestic Work as Decent Work: An Empirical Test of the Predictors of Decent Work To Extend the Psychology of Working Theory - Vollenhoven, Tarquin (Organisational Psychology, 2021)
The Psychology of Working Theory (PWT) focuses specifically on the work-based experiences of low-income workers. It is thus a suitable theoretical framework to predict and explain the work experiences of individuals performing domestic work, one of the largest work sectors in South Africa. The purpose of this study was to determine whether the theoretically derived predictors of decent work, in the PWT, could be empirically supported. Domestic workers, in Cape Town and Johannesburg, participated in a self-report survey (N = 139), which consisted of several measures. These participants were accessed through a variety of convenience and snowball sampling techniques. As expected, exploratory factor analysis revealed that the scales used to measure marginalisation, economic constraints, work volition and proactive personality were one-dimensional, and the decent work scale was fivedimensional (complementary values, access to health care, adequate compensation, free time and rest, and safe work conditions). Unexpectedly, the social support scale showed two dimensions (i.e. support from the community or friends and support from a special person or family). The findings supported the proposition that greater economic constraints were related to less decent work experiences, but marginalisation experiences were not related to the degree to which work was seen as decent, nor to work volition (mediator variable). The non-significant relationship between marginalisation, work volition and decent work changed when considering proactiveness as a moderator, however, this was only at low levels of proactiveness. None of the dimensions of social support served as moderators, though social support from the community or friends predicted work volition, and social support from a special person or family predicted the degree to which domestic workers experienced their work as decent. While there were mixed results, the findings of this study suggest that the PWT's antecedents and moderators may work differently in the domestic work sector. Future research should investigate this in the domestic work sector and other low-income samples.